General Modeling Language Supporting Model Transformations of MBSE (Part 2). Issue 1 (30th September 2020) - Guo, Jiangmin; Wang, Guoxin; Lu, Jinzhi; Ma, Junda; Törngren, Martin
Abstract: With the increasing complexity of systems, model‐based systems engineering (MBSE) has attracted increasing attention in the industry. MBSE formalizes the whole lifecycles of products using models based on systems engineering aiming to improve the development efficiency of complex systems. Traditionally, MBSE approaches require many modeling languages in each phase of the entire lifecycle. Different syntax between such languages leads to difficulty in supporting an integrated description of transformations between models and data. Thus, it is challenged to utilize a general language to describe model formalism and transformation for architecture‐driven technology and code generation in one MBSE tool. In this paper, a multi‐architecture modeling language called Karma (introduced in Paper Part 1) is proposed to support the model transformations including architecture‐driven technology and code generation implementations in one modeling tool. Finally, from one auto‐braking case of an autonomous‐driving system, we find the availability of the Karma language supporting architecture‐driven technology and code generation is verified.